Cost-benefit analysis of retrofitted non-engineered and engineered buildings in Nepal using probabilistic approach. Issue 122 (July 2019) - Dumaru, Rakesh; Rodrigues, Hugo; Varum, Humberto
Abstract: The applicability and suitability of the retrofit techniques adopted to enhance the seismic performance of the existing pre-engineered and non-engineered buildings were investigated through probabilistic cost-benefit analysis. The primary objective of the study aims to support, motivate, and encourage the decision makers, owners, investors, and concerned stakeholders to invest money for retrofitting of existing seismic deficient buildings. The study also aims to identify the best retrofit technique through the comparison of cost-benefit ratio. For this, the study investigates four existing buildings, representing two buildings for each non-engineered and pre-engineered design approaches. The selected non-engineered buildings were built in late 90's and pre-engineered buildings between late 90's to 2015. After rigorous analysis, it was revealed that the unexpected losses (in terms of monetary values) could be minimized by large extents, i.e. (2-11) times for non-engineered and (3-50) times for engineered buildings with the intervention of retrofit strategies. The attained expected annual loss for as-built and retrofit buildings evaluated through discrete distribution as a function of two intensity measures reveals that the maximum expected annual loss ensues between 0.1g and 0.2 g PGA for non-engineered buildings and below 0.1 g PGA for pre-engineered buildings. A higher cost-benefit ratio value can be attained if the service life of the building structure is increased or decreased discount rate. For most of the studied buildings, buildings retrofitted with RC shear wall found to be the most economically viable, and followed by steel bracing and jacketing, respectively. Highlights: Four existing buildings, representing two buildings for each non-engineered and engineered design approaches we studied. Support decision makers, owners, investors to invest money for retrofitting of existing seismic deficient buildings. Identify the best retrofit technique through the comparison of cost-benefit ratio.